Urinary biomarkers improve prediction of AKI in pediatric cardiac surgery - Deal, Oscar T.; Mitchell, Thomas; Harris, Amy G.; Saunders, Kelly; Madden, Julie; Cherrington, Carrie; Sheehan, Karen; Baquedano, Mai; Kanyongo, Rusununguko; Parolari, Giulia; Phillips, Kirsty; Stoica, Serban; et al. (Frontiers in Pediatrics, 2025)
Acute kidney injury (AKI) is a common postoperative complication of paediatric congenital heart disease (CHD) surgery, associated with increased morbidity and mortality. Current diagnostic approaches are unreliable in the early postoperative period, delaying diagnosis and treatment. This study investigates the efficacy of inflammatory and renal biomarkers in the early detection of postoperative AKI in paediatric CHD surgery patients. Biomarkers were assessed in urine and serum samples collected pre- and 24 h postoperatively from paediatric patients (median age 27 weeks) undergoing corrective CHD surgery (n = 76). Univariate and subsequent multivariate regression analysis with least absolute shrinkage and selected operator (LASSO) regularisation was performed to identify key predictors stratified by AKI diagnosis at 48 h. Significant biomarkers were included in a compound regression model which was evaluated through receiver operator curve analysis. Internal validation of the models was carried out through bootstrapping. Postoperative urine concentrations of interleukin-18 were significantly higher in those with postoperative AKI (p = 0.015), whereas uromodulin concentrations were lower (p = 0.010). Uromodulin, interleukin-18, and serum Fatty Acid Binding Protein 3 were associated with AKI (p = 0.011, 0.040, 0.042 respectively), with uromodulin and interleukin-18 performing strongly in a compound model withstanding LASSO regularisation, demonstrating an area under the curve of 0.899, sensitivity of 0.741, and specificity of 0.913. Urine uromodulin and interleukin-18 can be used to accurately predict postoperative AKI when measured at 24 h after surgery. Prompt recognition of postoperative AKI would facilitate early intervention, potentially mitigating the most severe consequences of renal injury.